Réponses

2014-06-03T18:16:33+02:00
(x-4)²- (x-2)(x-8)
x² - 8x +16 - (x² - 8x -2x +16)
= x² - 8x +16 - x² +8x +2x -16
= 2x

9996au carré -9998*9992
= (10 000 -4)² - (10000 -2)(10000 - 8)
= 10 00000 - 80 000 + 16 - 1000000 + 80 000 + 20000 - 16
= 20 000

Meilleure réponse !
  • Utilisateur Brainly
2014-06-03T18:27:28+02:00
(x - 4)² - (x - 2)(x - 8)
= x² - 8x + 16 - (x² - 8x - 2x + 16)
= x² - 8x + 16 - x² + 8x + 2x - 16
= x² - x² + 8x - 8x + 16 - 16 + 2x
= 2x

9 996² - 9 998 * 9 992
= (10 000 - 4)² - (10 000 - 2)(10 000 - 8) ⇒ 10 000 étant x.
= 1 000 000 - 80 000 + 16 - (1 000 000 - 80 000 - 20 000 + 16)
= 1 000 000 - 80 000 + 16 - 1 000 000 + 80 000 + 20 000 - 16
= 1 000 000 - 1 000 000 + 80 000 - 80 000 + 16 - 16 + 20 000
= 20 000